Synthesis of Al[2]O[3]-ZrO[2] powders from differently concentrated suspensions with a spray drying technique; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Lyamina G. V. Galina Vladimirovna; Ilela A. E. Alfa Edison; Khasanov O. L. Oleg Leonidovich; Petyukevich M. S. Mariya Stanislavovna; Vaytulevich (Vaitulevich) E. A. Elena Anatolievna (Synthesis and physicochemical characteristics of materials, 2016)
Title screen